2014
DOI: 10.1523/jneurosci.3700-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Profiles of Deafness in the Context of Native Language Experience

Abstract: The study of congenitally deaf adult humans provides an opportunity to examine neuroanatomical plasticity resulting from altered sensory experience. However, attributing the source of the brain's structural variance in the deaf is complicated by the fact that deaf individuals also differ in their language experiences (e.g., sign vs spoken), which likely influence brain anatomy independently. Although the majority of deaf individuals in the United States are born to hearing parents and are exposed to English, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 36 publications
2
71
1
2
Order By: Relevance
“…In addition to the evidence presented above, which suggests that language use (speech and sign) in deaf individuals might result in different crossmodal plasticity in primary auditory areas, the fact that the grey and white matter volume in several brain structures changes according to language experience in deaf individuals, suggests that results from deaf native signers cannot be generalised (Olulade et al, 2014). Characterising which of the components of plastic reorganisation in primary auditory areas of deaf individuals are caused by language modality and which by auditory deprivation is not only important for understanding the basic mechanisms of plastic reorganisation, but also because of its relevance in terms of approaches to language acquisition in deaf children, in particular those who have cochlear implants (CI) or are waiting to receive one.…”
Section: Introductionmentioning
confidence: 93%
“…In addition to the evidence presented above, which suggests that language use (speech and sign) in deaf individuals might result in different crossmodal plasticity in primary auditory areas, the fact that the grey and white matter volume in several brain structures changes according to language experience in deaf individuals, suggests that results from deaf native signers cannot be generalised (Olulade et al, 2014). Characterising which of the components of plastic reorganisation in primary auditory areas of deaf individuals are caused by language modality and which by auditory deprivation is not only important for understanding the basic mechanisms of plastic reorganisation, but also because of its relevance in terms of approaches to language acquisition in deaf children, in particular those who have cochlear implants (CI) or are waiting to receive one.…”
Section: Introductionmentioning
confidence: 93%
“…Unlike children with prelingual deafness and patients with post lingual deafness, the listening performance of adults with prelingual deafness was usually observed with enormous variability among individual and lower speech perception abilities [1] due to the cortical colonization and reorganization by other sensory modalities [2,3]. The slow progress of listening performance was shown in this 33 years old gentleman.…”
Section: Discussionmentioning
confidence: 94%
“…These two interpretations are not easy to disentangle. Olulade et al (2014) showed that cortical plasticity resulting from deafness depends on language experience for auditory and visual areas. If normally hearing participants who are CS-users (parents, teachers, educators of deaf CS-users) also showed activation of posterior STS, the hypothesis that multi-signal integration inside the visual modality occurs in this region of the brain would be reinforced.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normally hearing individuals, deaf native users of spoken language have fewer areas of anatomical differences than do deaf native users of ASL (Olulade et al, 2014). The neural processes involved in CS and in AV speech seem, to a certain extent, also similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation